A Novel E-Shapped DGS Incorporated Implantable Antenna for Biomedical Applications - G. Shankara Bhaskara Rao; P. K. R. Bhagya Lakshmi; V. Pradeep Reddy; P. Priyanka; N. Maruthi; KATARIA, S.B.S.S. Raja (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This paper represents designing & analysis of E-shape microstrip patch antenna for wireless communication. Low volume, low profile configuration, easily mounted, light weight,,low fabrication cost is the advantages of this antenna. The operating frequencies of antenna are 2.4 GHz  the substrate RT DUROID 5880 is used for proposed antenna with dielectric constant (2.2) and thickness of (1.0mm). Two slots are cut to form the E-shape , which provides a bandwidth of 400 mhz . The E-shape has return loss of -15.49dB and gain of 7.1dB at operating frequencies 2.4 GHz respectively. Designing and simulation of this antenna has been done by the help of HFSS Software. This antenna is fed by a co-axial probe feeding.In this paper, the effects of different types of antenna parameters studied.
Keywords: Co-Axial Feed Antenna; Compact Wireless Antenna; Microstrip Patch Antenna; Patch Antenna; E-Shaped Antenna; HFSS